Perancangan sistem informasi manajemen persediaan barang untuk usaha Mikro kecil dan menengah (UMKM) : Studi kasus pada toko arkhan jaya - Andika Pratama; Rizka Hafsari (Computer Science and Information Technology, 2024)
In the current digitalization era and the increasing demand for efficiency, flexibility is a crucial aspect for the continuity of Small and Medium Enterprises (UMKM) in Indonesia. This research aims to design a more effective and efficient inventory management system for Arkhan Jaya, a UMKM in Indonesia. The system is expected to assist the management in reducing human errors, increasing productivity, and improving the accuracy of inventory information. The waterfall research methodology is used, which includes system requirements analysis, system architecture design, data technology design, system testing, and maintenance.During the analysis phase, specific needs of Toko Arkhan Jaya are identified to ensure that the developed system is suitable. The design phase produces a system architecture that includes a database, user interface, and functional modules. The design phase involves coding the main modules, system configuration, and user training. Testing is carried out to ensure that the system functions according to specifications, focusing on inventory management, purchasing, and sales processes.The research findings indicate that the designed information system can increase inventory management efficiency, enable quick and accurate decision-making, and provide accurate and real-time inventory information. This research contributes to improving inventory management in UMKMs.